Comparative Analysis of the Application of Roychowdhury and Gunny Models in the Estimation of Real Earnings Management - Comporek, Michał (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: The main aim of the article is to present the results of empirical research on the formation of abnormal production costs as well as discretionary SG&A expenditures in public companies included in the WIG-construction index. A secondary goal is to analyse the relationship between the scope of implemented real earnings management practices and the performance of listed companies, assessed on the basis of the ROA coefficient.Research Design & Methods: Analytical formulas of Roychowdhury and Gunny models were used to determine the scale of real earnings management.Findings: The empirical research shows that in the studied population there are statistically significant relationships between the achieved ROA coefficient and the scale of implemented REM practices. The relationships between REM coefficients, distinguished by different regression models, are shown to be very strong.Implications / Recommendations: The method used to estimate the level of discretionary SG&A expenditures has a greater impact on the overall assessment of the scale of REM practices in an enterprise than do discretionary production costs.Contribution: The research should contribute to the search for effective instruments for measuring company activities related to the intentional shaping of financial results.